MEMBUMIKAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM KELUARGA DI-ERA GLOBALISASI - Ruqoiyah Ruqoiyah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2018)
Education is a conscious and planned effort to realize the atmosphere, learning process and learning process so that students actively develop their potential to have religious spiritual strength, self-control, intelligence, noble character, and skills, which are needed by themselves, the nation and the state. The National Education Objective is